A reader's guide to the novels of Louise Erdrich - Beidler, Peter G. (University of Missouri Press, 2006)
"A revised and expanded, comprehensive guide to the novels of Native American author Louise Erdrich from Love Medicine to The Painted Drum. Includes chronologies, genealogical charts, complete dictionary of characters, map and geographical details about settings, and a glossary of all the Ojibwe words and phrases used in the novels"--Provided by publisher.